Effect of irradiation wavelength on the heterogeneous photocatalytic removal of organic pollutants using TiO2 and ZnO - Náfrádi Máté (Proceedings of the International Symposium on Analytical and Environmental Problems, 2021)
The efficiency of TiO2 and ZnO was compared during the photocatalytic removal of neonicotinoid pesticides (imidacloprid and thiacloprid) and sulfonamide antibiotics (sulfamethazine and sulfamethoxypyridazine), causing severe environmental and health problems. The differences between LEDs emitting at 365 nm and 398 nm were compared, and removal efficiencies were tested in tap water and biologically treated wastewater matrices. The effect of the most abundant anions, Cland HCO3 on the removal efficiency and •OH formation was also compared. TiO2 was more sensitive to the matrices and the irradiation wavelength. •OH production was higher for TiO2, and 398 nm photons resulted in a higher contribution of •OH. Efficiencies were not reduced by matrix components for ZnO, which is mainly the result of increased •OH-production by Cl- . In the case of TiO2 and 365 nm photons, the formation of CO3 from HCO3 -was assumed. For TiO2, the significant inhibition of matrices could not be explained solely by the effect of anions.